Challenges of implementing a large scale larviciding campaign against malaria in rural Burkina Faso – lessons learned and recommendations derived from the EMIRA project. (December 2016) - Dambach, Peter; Traoré, Issouf; Kaiser, Achim; Sié, Ali; Sauerborn, Rainer; Becker, Norbert
Abstract Background Recent malaria control and elimination attempts show remarkable success in several parts of sub-Saharan Africa. Vector control via larval source management represents a new and to date underrepresented approach in low income countries to further reduce malaria transmission. Although the positive impact of such campaigns on malaria incidence has been researched, there is a lack of data on which prerequisites are needed for implementing such programs on a routine basis on large scale. Our objectives are to point out important steps in implementing an anti-malaria larviciding campaign in a resource and infrastructure restraint setting and share the lessons learned from our experience during a three-year intervention study in rural Burkina Faso. Methods We describe the approaches we followed and the challenges that have been encountered during the EMIRA project, a three-year study on the impact of environmental larviciding on vector ecology and human health. An inventory of all performed work packages and associated problems and peculiarities was assembled. Results Key to the successful implementation of the larviciding program within a health district was the support and infrastructure from the local research center run by the government. This included availability of trained scientific personnel for local project management, data collection and analysis by medical personnel, entomologists and demographers and teams of fieldworkers for the larviciding intervention. A detailed a priori assessment of the environment and vector breeding site ecology was essential to calculate personnel requirements and the need for larvicide and application apparel. In our case of a three-year project, solid funding for the whole duration was an important issue, which restricted the number of possible donors. We found the acquisition of qualified field personnel in fair numbers not to be always easy and training in application techniques and basic entomologic knowledge required several weeks of theoretical and practical formation. A further crucial point was to establish an effective quality control system that ensured the timely verification of larviciding success and facilitated in time data handling. While the experiences of running a larviciding campaign may vary globally, the experiences gained and the methods used in the Nouna health district may be employed in similar settings. Conclusions Our observations highlight important components and strategies that should be taken into account when planning and running a similar larviciding program against malaria in a resource limited setting. A strong local partnership, meticulous planning with the possibility of ad-hoc adaption of project components and a reliable source of funding turned out to be crucial factors to successfully accomplish such a project.